Faktor-Faktor yang Mempengaruhi Kepatuhan ODHIV dalam Terapi ARV di Dunia Tahun 2018 - 2022 - Marlysawati, Dewi; Sudaryo, Mondastri Korib (STIKES Adi Husada, 2024)
ARV therapy is important in treating HIV cases. Even though it does not cure, ARVs help suppress the growth of the virus. Adherence to therapy is essential to achieve optimal results. The objective was to decide the components that impact the adherence of PLHIV in ARV treatment. This could be a story writing audit think about conducted by looking at articles through the Science Coordinate and PubMed databases. The catchphrases utilized are Variables impacting adherence to antiretroviral treatment among HIV/AIDS patients, HIV patient adherence to ART, and